2000
DOI: 10.1097/00000421-200004000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of Three-Dimensional Conformal Radiotherapy as Salvage Treatment for a Rising Prostate-Specific Antigen Level Postprostatectomy

Abstract: The purpose of this study is to determine the effectiveness of three-dimensional conformal radiotherapy delivered to the fossa of the prostate and seminal vesicles as salvage treatment for a prostate-specific antigen (PSA) level that becomes undetectable and subsequently begins to rise postprostatectomy. Between August 1994 and December 1997, 14 patients with prostate cancer whose PSA became undetectable after a radical prostatectomy subsequently developed a rising PSA, had no evidence of metastatic disease, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Results vary between 10 and 73%, with different patient selection criteria being the most probable explanation for that enormous divergence (table 3) [13,18,29,[31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Pooled data from 6 larger studies show a PSA decrease into the unde- [46] reported on 53 patients, more than half of whom had persisting PSA levels after RP and therefore possibly a worse prognosis.…”
Section: Results Of Salvage Rtmentioning
confidence: 99%
“…Results vary between 10 and 73%, with different patient selection criteria being the most probable explanation for that enormous divergence (table 3) [13,18,29,[31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Pooled data from 6 larger studies show a PSA decrease into the unde- [46] reported on 53 patients, more than half of whom had persisting PSA levels after RP and therefore possibly a worse prognosis.…”
Section: Results Of Salvage Rtmentioning
confidence: 99%
“…A low pretreatment PSA level is an important factor for sRT to be successful. The borderline value of PSA for excellent results of sRT is 1.5 and 2.0 ng/ml, respectively [29][30][31][32][33][34][35][36][37] . Other prognostic factors for the efficacy of sRT are: PSADT [38][39][40][41][42] , PSA before RP [22,23] , seminal vesicle invasion [23,24,27,43,44] and extracapsular extension [27,43,44] .…”
Section: Discussionmentioning
confidence: 99%
“…Previously published reviews 62–64 have found long term rates of GU toxicity (≥grade 2) to be in the range of 0–10%, 51,52,65–77 and GI toxicity rates (≥grade 2) in the range of 0–10% 44,65,66,77,78 …”
Section: Toxicity Of Srtmentioning
confidence: 98%
“…Previously published reviews [62][63][64] have found long term rates of GU toxicity (Նgrade 2) to be in the range of 0-10%, 51,52,[65][66][67][68][69][70][71][72][73][74][75][76][77] and GI toxicity rates (Նgrade 2) in the range of 0-10%. 44,65,66,77,78 Several studies have looked at health related quality of life outcomes following SRT.…”
Section: Toxicity Of Srtmentioning
confidence: 99%